Formação, atualização profissional e nível de conhecimento técnico dos profissionais atuantes em academias da cidade de Pelotas RS - Salerno, Mateus (2013)
In recent decades, Brazil has experienced growing in the number of specialized agencies, service providers on physical and sports activities: gyms. It is believed that there are approximately 20,000 establishments in the country that offer various activities of gymnastics, weightlifting, dancing, water activities and martial arts, which absorb about 60% to 70% of Physical Education professionals entering the job market each year. Many of them still do not absorb trained professionals, such as provisioned, students and laymen. Very little is known about the portion that represents each of these groups within the workforce working in gyms. Moreover, we particularly do not have information on technical knowledge and professional update of these workers, two aspects that are essential to work satisfactory in these places. Thus, the present study aimed to evaluate the level of technical knowledge and professional development of professional gyms essential for planning and implementation of a physical training program for gym users in the city of Pelotas - RS. Descriptive, observational, cross-sectional study covering all professionals working in gyms of physical activity in the city. Data collection will be conducted using a pre-tested questionnaire and codified, including questions about demographic and socioeconomic conditions, on training, technical knowledge and professional development